CHALLENGES AND STRATEGIES FOR TERMINOLOGICAL CLARITY IN COMPUTER LINGUISTICS - Nigora Satibaldieva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This paper delves into the intricate challenge of polysemy within computational linguistics, a field uniquely positioned at the intersection of language and technology. Polysemy, the phenomenon of multiple meanings for a single term, is both a linguistic richness and a computational hurdle. The paper discusses how diverse meanings of terms in different subfields can lead to ambiguities in computational models. The paper also explores various polysemy types, including homonymy, metaphorical extension, and syntactic ambiguity, highlighting their implications for natural language processing and professional communication. Emphasizing the need for standardized terminology, the paper suggests strategies like comprehensive glossaries and consensus building. Through case studies and future research directions, it underscores the importance of tackling polysemy for advancing clarity in computational linguistics.